DCK Expression and Gene Polymorphism With Gemcitabine Chemosensitivity in Patients With Pancreatic Ductal Adenocarcinoma: A Strobe-Compliant Observational Study. Issue 10 (March 2016) - Xiong, Junjie; Altaf, Kiran; Ke, Nengwen; Wang, Yichao; Tang, Jie; Tan, Chunlu; Li, Ang; Zhang, Hao; He, Du; Liu, Xubao
Abstract : Abstract: The aim of this study was to investigate the relationship of deoxycytidine kinase (dCK) protein expression and gene single-nucleotide polymorphisms to gemcitabine chemosensitivity in patients with pancreatic ductal adenocarcinoma (PDAC). In total, 54 patients with resectable PDAC, who received postoperative gemcitabine-based therapy, were enrolled in this study, from January 2011 to April 2013. The dCK protein expression was measured retrospectively by immunohistochemistry. Furthermore, 5 single-nucleotide polymorphisms (C1205T, A9846G, A70G, C356G, and C364T) of the dCK gene were detected in PDAC cells by PCR amplification and sequencing. The dCK protein expression was found to be negatively correlated with age ( P  = 0.006), but correlated positively with overall survival (OS) ( P  = 0.000) and disease-free survival (DFS) ( P  = 0.003). The A9846G AA genotype in the dCK gene was significantly associated with reduced mortality compared with AG and GG genotypes. The OS and DFS were longer in patients with the A9846G AA genotype than the AG and GG genotypes. In univariate and multivariate analyses, we found that the dCK protein expression and A9846G genotype were significant predictors of both OS and DFS. Our study suggests that the dCK protein expression and A9846G genotype may act as prognostic biomarkers in identifying patients who are likely to benefit from postoperative gemcitabine therapy in PDAC.